2014 IEEE Conference on Control Applications (CCA) 2014
DOI: 10.1109/cca.2014.6981393
|View full text |Cite
|
Sign up to set email alerts
|

Multivariable control for regulating high pressure centrifugal compressor with variable speed and IGV

Abstract: The objective of this paper is to develop a multivariable control system for a class of centrifugal compressors, which exploit as control signals both the rotational speed and the Inlet Guide Vane (IGV). Linear Quadratic Gaussian control with Integral action (LQGI) and Model Predictive Control (MPC) are investigated. The LQGI and MPC controllers are compared to a standard proportional integral (PI) controller, to regulate the discharge pressure of the compressor. The control algorithms are simulated and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The turbo air compressor can be modeled using compressor maps derived through the computational fluid dynamics (CFD) analysis. The mechanical model of the turbo air compressor can be expressed by the corrected air flow rate m corr , pressure ratio PR, and corrected rotational speed N corr as follows [9]:…”
Section: Mechanical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The turbo air compressor can be modeled using compressor maps derived through the computational fluid dynamics (CFD) analysis. The mechanical model of the turbo air compressor can be expressed by the corrected air flow rate m corr , pressure ratio PR, and corrected rotational speed N corr as follows [9]:…”
Section: Mechanical Modelmentioning
confidence: 99%
“…In particular, the multi-level inverter can operate medium voltage and high voltage induction motors, and is applied to large air compressor systems such as screw compressors and centrifugal turbo compressors. Centrifugal turbo air compressors have high operating efficiency, but have a narrow operating range of 70% to 100% [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distance of the operating point, displayed as a red dot, from the SL and the SCL defines, respectively, the SD and surge control distance (SCD) [18], [22], [39]. The choke line (CL) is a maximum mass flow rate limit that, in contrast to the surge related lines, cannot be physically reached by the machine, and hence is not considered in the control problem.…”
Section: A Mathematical Modelmentioning
confidence: 99%
“…The benefits to the industrial implementation are shown experimentally in [17], where it is observed that tuning the standard PI control for surge avoidance becomes extremely difficult in the presence of external disturbances, since a specific tuning for one scenario can be ineffective for all others. In [18], a linearized MPC is employed for a compression system, driven by a gas turbine, which controls the rotor speed and the inlet guide vane positioning. A configuration with a recycle valve is used in [19].…”
Section: Introductionmentioning
confidence: 99%